Variation of skeletal degenerative joint disease features in an identified Italian modern skeletal collection. Issue 4 (28th April 2016) - Zampetti, Stefania; Mariotti, Valentina; Radi, Nico; Belcastro, Maria Giovanna
ABSTRACT: Objectives: The objective of this study was to investigate the relationship of degenerative joint disease (DJD) features (marginal lipping, porosity, surface osteophytes, eburnation, and loss of joint morphology) with sex, age, and occupation. Materials and Methods: We devised a recording method for scoring the single features in the shoulder, elbow, wrist, hip, knee, and ankle of an Italian skeletal sample of 332 individuals (males = 161, females = 171) of known sex, age, and occupation from the Frassetto collection (Sassari, Sardinia, 19th–20th century). Results: Our data revealed that: (1) the frequency of all features increases with age; (2) porosity is the first feature to appear, being in general the most frequent feature in young adults; (3) sex differences are especially found in the upper limbs of mature and elderly adults; (4) marginal lipping and surface osteophytes show a lesser age correlation and, in general, higher frequencies in the left lower limb; (5) no differences were found among different occupations. Discussion: We explain these results in light of different metabolic and adaptive processes in relation to age and sex. Static (weight‐bearing) rather than dynamic mechanical stress could play a pivotal role in the distribution of the features observed in the lower limbs. The considerable increase in marginal lipping and surface osteophytes in elderly adults may be an adaptation for sustaining mechanical loading, balancing the loss of bone tissue which is characteristic of ageing processes (osteopenia, osteoporosis). Am J Phys Anthropol, 2016. © 2016 Wiley Periodicals, Inc. Am J Phys Anthropol 160:683–693, 2016. © 2016 Wiley Periodicals, Inc.